Convergence behaviour — packing relations of full extraction gate roadways at OAL lignite mine - Y. S. Istanbulluoglu; C. Karpuz (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
This paper describes the results of convergence measurements conducted about five years for the re-use gate roadways at OAL lignite mine in Turkey. Double lignite seams separated with a marn layer, are mined with long-wall retreating mining system at the mine. Rib pillar has been abandoned and gate roadways were planned to be packed for the re-use of full extraction. Various packing systems have been attempted, namely three rows of woodenchock, one row of wooden chock plus concrete wall and concrete wall only. The re-use of maingate roadways packed with wooden chock yielded 62% of closure. Lastly developed concrete packing of 3 meters wide and specially developed support set composed of three friction props and a cap, which is a modification of yieldable set, have successfully maintained the main and tail gate roadways stability with a total vertical convergence of 32%. Good correlation has been established between pack stiffness and floor heave as well as maingate and tailgate convergences. The elimination of rib pillars by re-use of gate roadways increased the coal recovery by 20% and decreased the development/production ratio from 0.065 m3/ton to0.022 m3/ton.